论耽改剧中同性爱的“罔两”位置 ：以《陈情令》为例 = An analysis of the "penumbra" position of homosexuality in the Dangai series : the untamed - 蔡茹薏 Chai, Ru Yi (Nanyang Technological University, 2021)
1990年代，描绘男男浪漫爱情故事的耽美文学从日本传入中国，其创作者和消费者多为女性。近年，部分著名耽美小说被改编成网络剧，但碍于中国大陆相关权力机构明令禁止网剧呈现同性恋内容，制片方只得把小说中的同性爱置换成“兄弟情”，耽改剧这一新类型亦由此诞生。制片方如何以“知己”一类同性友好话语置换同性爱是本文关注的重点。网络耽改剧《陈情令》改编自墨香铜臭的耽美小说《魔道祖师》，本文以《陈情令》为研究对象，参考“罔两问景”方法学，把文化建构的“社会性”设为“形”、影视作品建构的“兄弟”框架设为对“形”亦步亦趋的“影”、剧中无法现身的同性爱则设为被人们所忽略的“罔两”。在吸引耽美爱好者及主流话语约束的双重夹击下，笔者发现制片方一面把小说中的同性爱情节转换成对视、搭肩等元素，一面企图通过强调“侠义”精神文化、增加异性恋情节、删减镜头等手法，把同性爱这个罔两驱赶到形影的阴影中。Danmei literature originated in Japan and was introduced to China during the 1990s. Despite its depiction of romantic male homosexual love stories, its creators and fan base mainly consists of females. In recent years, several well-received Danmei novels were adapted to become web series. However, producers altered the characters’ homosexuality into homosociality. Hence, a new genre was born-- Dangai. This thesis focuses on the methodology that was used by the producers to modify the original works by masquerading themes of “love” into themes of “friendship”. This research paper centres on the web series entitled The Untamed, a Dangai series adaptation of the Danmei novel MoDaoZuShi which was written by MoXiangTongXiu. This paper refers to the “Penumbrae Query Shadow Methodology”. “Shape” and “Shadow” is seen as a metaphor, where “Shape” represents the social construction of sexuality, and “Shadow” represents the non-sexual homosocial discourse which built by the producers. “Shadow” is always confined within the “Shape” and will always follow without question. The “Penumbrae”, however, is the lighter-toned outer shadows and signifies those that defy patriarchal culture, which in here is homosexuality. In order to attract the Danmei lovers, the producers of The Untamed replaced all sexually explicit scenes that involved physical contact into mutual staring and placing hand on shoulder. However, due to the strict laws being imposed on China, the producers utilised conventional themes of chivalry, inserted heterosexual romances and deleted specific scenes to replace homosexual love.